Butyrate inhibits the mitochondrial complex Ι to mediate mitochondria-dependent apoptosis of cervical cancer cells - Ke Zhang; Xiawei Ji; Zhengyang Song; Wenjing Song; Qunjia Huang; Tiantian Yu; Dibang Shi; Fangyan Wang; Xiangyang Xue; Junping Guo (BMC, 2023)
Abstract Background Cervical cancer (CC) is a common gynecological malignancy with high morbidity worldwide. Butyrate, a short-chain fatty acid produced by intestinal flora, has been reported to inhibit cervical carcinogenesis. This study aimed to investigate the pro-apoptotic effects of butyrate on CC and the underlying mechanisms. Methods Human HeLa and Ca Ski cells were used in this study. Cell proliferation, cell migration and invasion were detected by CCK-8 and EdU staining, transwell and wound healing assay, respectively. Cell cycle, mitochondrial membrane potential and apoptosis were evaluated by flow cytometry. Western blot and RT-qPCR were carried out to examine the related genes and proteins to the mitochondrial complex Ι and apoptosis. Metabolite changes were analyzed by energy metabolomics and assay kits. The association between G protein-coupled receptor 41, 43, 109a and CC prognosis was analyzed using data from The Cancer Genome Atlas (TCGA). Results CCK-8 results showed significant inhibition of CC cell proliferation induced by butyrate treatment, which was confirmed by EdU staining and cell cycle detection. Data from the transwell and wound healing assay revealed that CC cell migration was dramatically reduced following butyrate treatment. Additionally, invasiveness was also decreased by butyrate. Western blot analysis showed that cleaved Caspase 3 and cleaved PARP, the enforcers of apoptosis, were increased by butyrate treatment. The results of Annexin V/PI staining and TUNEL also showed an increase in butyrate-induced apoptotic cells. Expression of Cytochrome C (Cytc), Caspase 9, Bax, but not Caspase 12 or 8, were up-regulated under butyrate exposure. Mechanistically, the decrease in mitochondrial NADH and NAD + levels after treatment with butyrate was observed by energy metabolomics and the NAD+/NADH Assay Kit, similar to the effects of the complex Ι inhibitor rotenone. Western blot results also demonstrated that the constituent proteins of mitochondrial complex Ι were reduced by butyrate. Furthermore, mitochondria-dependent apoptosis has been shown to be initiated by inhibition of the complex Ι. Conclusion Collectively, our results revealed that butyrate inhibited the proliferation, migration and invasion of CC cells, and induced mitochondrial-dependent apoptosis by inhibiting mitochondrial complex Ι.